YHWH Ekhad dalam Ulangan 6:4 sebagai Dasar Panggilan Pengajaran Monoteis - Noh Ibrahim Boiliu (SANCTUM DOMINE: JURNAL TEOLOGI, 2023)
The issue of Deuteronomy 6:4, which includes the monotheistic creed of Shema Yisrael, is often interpreted solely in the context of monotheistic dogmatics. Deuteronomy 6:4 is not limited to the framework of monotheistic dogma but also has an educational and legal dimension that shapes the moral identity of Israel. This article is an attempt to develop the concept that within the teaching of monotheism lies an effort to form the moral and identity of believers. The article proposes the idea that the call "Hear, O Israel" reflects a rhetoric repeated in Deuteronomy, and the imperative verb "to hear" is considered a fundamental call to monotheistic dogma. Israel's response to this call is deemed crucial because listening to God is indicated by remaining faithful to monotheistic dogma and loving God wholeheartedly. The call to listen is conveyed to the new generation of Israel. The importance of listening and responding to this call is illustrated through the phrase "Shema Israel," which asks Israel to acknowledge that Yahweh is One. Yahweh Ekhad has an educational and legal role in shaping and affirming the moral identity of Israel by emphasizing the importance of teaching and observing the law in response to the call to listen. The relationship between monotheism, religious education, and moral identity in the context of Deuteronomy 6:4 emphasizes the importance of listening and responding to God's call as the foundation for obedience and realization of the monotheistic identity of Israel.